Carbon nanofibers as potential materials for catalysts support, a mini-review on recent advances and future perspective - Din, I.U. (Elsevier Ltd, 2020)
The element carbon has been used as an active catalyst as well as a catalyst support. This dual nature of carbon has been attributed to its characteristics such as high porosity, large surface area, excellent electron conductivity and chemical inert nature. Besides, the availability of different forms of carbon like graphene, activated carbon, carbon nanotubes and carbon nanofibers have provided carbon a versatile material to be used for different applications. Carbon has been widely used in different applications like electrical, bio-electrochemical, dry cells, electrodes and as a lubricant. However, in the last decades, the catalytic applications of carbon materials especially carbon nanotubes and carbon nanofibers have gained tremendous attention of the researchers worldwide. Carbon nanofibers, in particular due to thier excellent catalytic support profile like, high surface area, thermal stability and its 3D access to the reacting molecules, have been utilized for different chemical reactions. Metal supported on carbon nanofibers have been observed with better activities as compared to the traditional supported counterparts for the several reactions. This mini-review attempts to document the role of carbon nanofibers and their catalytic support profile for the some common chemical processes. The mini-review also suggests about the future innovations and research work for carbon nanofibers as potential future catalysts support. Â© 2020 Elsevier Ltd and Techna Group S.r.l.